26th Joint Propulsion Conference 1990
DOI: 10.2514/6.1990-1981
|View full text |Cite
|
Sign up to set email alerts
|

Shock enhancement and control of hypersonic mixing and combustion

Abstract: The possibility that shock enhanced mixing can substantially increase the rate of mixing between coflowing streams of hydrogen and air has been studied in experimental and computational investigations. Early numerical computations indicated that the steady interaction between a weak shock in air with a coflowing hydrogen jet can be well approximated by the two-dimensional time-dependent interaction between a weak shock and an initially circular region filled with hydrogen imbedded in air. An experimental inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 6 publications
(3 reference statements)
1
34
0
Order By: Relevance
“…Large-scale stirring of the flow field will result directly in increased molecular-scale mixing as the interfacial area between the two gases in increased and species gradient dimensions decreased. Further, Marble et al 5 showed that the time-scale on which the mixing occurs is short enough to be of interest for combustion enhancement in scramjet applications.…”
Section: Shock-enhanced Mixingmentioning
confidence: 99%
See 1 more Smart Citation
“…Large-scale stirring of the flow field will result directly in increased molecular-scale mixing as the interfacial area between the two gases in increased and species gradient dimensions decreased. Further, Marble et al 5 showed that the time-scale on which the mixing occurs is short enough to be of interest for combustion enhancement in scramjet applications.…”
Section: Shock-enhanced Mixingmentioning
confidence: 99%
“…A geometry was conceived in April 1987 and presented by Marble et al 5 • A diagram of the injection geometry is shown in Figure I. The injector consists of alternate compression ramps and expansion troughs.…”
Section: The Contoured Wall Fuel Injectormentioning
confidence: 99%
“…Such influences can subsequently lead to the interactions of a shock-mixing layer and shock-boundary layer inside the combustor. While the shockmixing layer interactions may enhance the overall mixing rate (Marble, 1990), the shock-boundary layer interactions may induce boundary layer separation and hence form a low-speed recirculation flow (Shapiro, 1953). Obviously, the induced boundary layer separation would cause problems for most hypermixer fuel injectors mounted on the combustor wall, since the local flow is preferred to be supersonic without separation (Drummond, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Such flow situations with high velocities and short residence times require that fuel and air mix and burn quickly to avoid excessively long combustors. It is well known that the shearlayer growth rate diminishes significantly with increasing convective Mach numbers, and as such, the mixing in high-speed flow is slow [1][2][3][4][5]. Various studies on slot injection into a supersonic flow have been reported in an attempt to enhance the mixing efficiency.…”
mentioning
confidence: 99%
“…Such transverse injection schemes have undergone diverse modifications to enhance the mixing characteristics. Novel techniques such as shock enhancement [2][3][4][5], two-stream injection [6,7], oscillating shock wave [8], hypermixing nozzles [9], controlled swirling injectors [10,11], and aeroramps [12,13] have been considered with varying success. A rather comprehensive review of various injection schemes has been carried out [14].…”
mentioning
confidence: 99%